Role of anti-DFS70 antibodies in ruling out connective tissue disorders in Antinuclear Antibody (ANA) positive patients: A Cross-Sectional Study. - Kumar, Sanjeet; Suman, Ravi Ranjan Kumar; Rajeev Ranjan; Kumar, Rajneesh (Student’s Journal of Health Research Africa, 2025)
Background Proteins are the target of Antinuclear Antibodies (ANAs), and the cell nucleus is where most nucleic acid antigens are found. The initial step in laboratory diagnosis for AARD is ANA detection. It is still difficult to comprehend the processes that underlie the production of ANAs in AARD and other chronic diseases of inflammatory. Objectives The purpose of conducting this study was to ascertain if isolated anti-DFS70 antibody positivity may be utilized to accurately rule out connective tissue disorders and to assess the value of diagnostics of anti-DFS70 antibodies in those individuals who are ANA-positive. Materials and Methods It was a cross-sectional, observational study. The study was carried out in the All-India Institute of Medical Sciences (AIIMS), Patna, Bihar, India. The study was conducted for 13 months. A total of 111 patients were enrolled. Results The average age of participants in the group of CTD was 40.1 ± 11.5 years, and CTD group age of participants 37.6 ± 12.6 years. Among all, 82 (73.9%) participants were female, and 29 (26.1%) participants were male. Isolated anti-DFS70 was seen in 16 patients, among them no participant had CTD, and all were non-CTD participants 16 (100%). Anti-DFS70 positive disease specific ENA was observed in 02 participants, and all the patients had CTD. Conclusion This study has revealed that isolated anti-DFS70 antibody positivity is quite specific for ruling out connective tissue disorders. Recommendation Routine testing for anti-DFS70 antibodies should be included in the diagnostic workup of ANA-positive patients to help effectively distinguish non-CTD cases and prevent unnecessary investigations.